Electrochemical Studies on Alizarin Red S as Negolyte for Redox Flow Battery: a Preliminary Study - Khor, C.; Mohamed, M. R.; Feng, C. K.; Leung, P. K. (International Journal of Engineering and Technology, 2018)
Redox flow battery (RFB) has received tremendous attention as energy storage system coupled with renewable energy sources. In this paper, a low-cost alizarin red S (ARS) organic dye is proposed to serve as the active material for the negative electrode reaction for organic redox flow batteries. Cyclic voltammetry has been conducted under a number of operating conditions to reveal the electrochemical performance of this molecule. The results suggest that ARS is highly reversible at low electrode potential (c.a. 0.082 V vs. standard hydrogen electrode), indicating that ARS is a promising negative electrode material for organic redox flow batteries. The diffusion coefficient of ARS is calculated in the range of 6.424 x 10-4 cm2 s-1, This has indicated fast diffusion rate and electrochemical kinetics for oxidation and reduction in higher concentration of ARS. It has been found out that the higher concentration of ARS in base electrolyte cause lowest diffusion coefficient due to solubility issue of ARS.